2009
DOI: 10.1002/jpln.200700220
|View full text |Cite
|
Sign up to set email alerts
|

Carbon dioxide enrichment by composting in greenhouses and its effect on vegetable production

Abstract: Concentrations of CO 2 are commonly suboptimal for plant production in greenhouses. Here, a new strategy using crop-residues and animal-manure composting (CRAM) was developed to increase CO 2 concentration throughout the day. During the whole cultivation period, CRAM-treated greenhouses had CO 2 concentrations that were more than twice that of the control greenhouses. This resulted in yields of celery (Apium graveolens L.), leaf lettuce (Lactuca virosa L.), stem lettuce (Lactuca saiva L.), oily sowthistle (Son… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 30 publications
2
37
0
Order By: Relevance
“…Super‐elevated CO 2 decreased nitrate and protein accumulation to the same extent with eCO 2 , which indicates that there was no additive improvement of fruit quality resulting from super‐elevated CO 2 as hypothesized. As the nitrate accumulation depends on the relative rates of nitrate assimilation and nitrate uptake, this study demonstrated that both CO 2 treatments inhibited the nitrate uptake to a greater extent than nitrate assimilation in the used soil, which is consistent with previous findings . Both CO 2 treatments, therefore, decrease the potential threats by toxic nitrite and/or N ‐nitroso compounds transformed from nitrate .…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Super‐elevated CO 2 decreased nitrate and protein accumulation to the same extent with eCO 2 , which indicates that there was no additive improvement of fruit quality resulting from super‐elevated CO 2 as hypothesized. As the nitrate accumulation depends on the relative rates of nitrate assimilation and nitrate uptake, this study demonstrated that both CO 2 treatments inhibited the nitrate uptake to a greater extent than nitrate assimilation in the used soil, which is consistent with previous findings . Both CO 2 treatments, therefore, decrease the potential threats by toxic nitrite and/or N ‐nitroso compounds transformed from nitrate .…”
Section: Discussionsupporting
confidence: 91%
“…The greater magnitude of carbohydrate accumulation may be attributed to the greater transformation of other compounds to glucose, starch, and dietary fiber. Elevated CO 2 has been shown to increase soluble sugar in vegetables like celery, tomato and lettuce, of starch in potato and palak, and of dietary fiber in carrot, radish, and turnip, which can enhance the taste flavor of fruits and alleviate the health risks caused by certain diseases (e.g. diabetes, cancer, and cardiovascular disease) due to potential greater intake of dietary fiber .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our results showed that the nutritional quality of Chinese cabbage grown in Cd-added soil was affected by different fertilization methods. Soluble sugar levels are used to evaluate the taste characteristics of vegetables and soluble protein accumulation as an indicator of value for human nutrition (Hurrell, 2003;Jin et al, 2009). The split applications produced a higher level of soluble sugar in the ammonium treatment, and a higher level of soluble protein in the nitrate treatment, compared with the single applica-tions.…”
Section: Discussionmentioning
confidence: 99%